ED50 for intravenous midazolam-induced amnesia and its duration in surgical patients - Yan, Jing; Gao, Chao; Wang, Yun; Wu, An-Shi; Yue, Yun (Annali italiani di chirurgia, 2021)
Intraoperative awareness is a serious adverse event under general anesthesia. Midazolam has a good anterograde amnesia-inducing effect, can prevent and reduce the occurrence of intraoperative awareness. However, if the dosage of midazolam is improperly controlled, it may not produce forgetting effect, or bring obvious adverse side effects, such as respiratory depression, and delay of recovery. However, the half maximal effective dose (ED50 ) of midazolam for amnesia, the duration of amnesia and the factors affecting the duration of amnesia are still inconclusive. Therefore, it is of great clinical significance to observe and determine the dose, duration and influencing factors of amnesia induced by midazolam METHODS: A total of 106 patients who underwent ASA grades I-II elective operation under spinal-epidural anesthesia were intravenously injected with different doses of midazolam at 10 minutes after spinal-epidural anesthesia, every 5 minutes, the patient was presented with pictures or sounds as memory content, and heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean blood pressure (MBP), blood oxygen saturation (SpO2), bispectral index (BIS), OAA/S and adverse events were recorded. The patient's forgetfulness was followed up in the early morning after operation. ED50 (the dose for amnesia in half of the subjects) was 0.031 mg/kg (95% CI: 0.027-0.036 mg/kg); ED95 (the dose for amnesia in 95% of the subjects) was 0.044 mg/kg (95% CI: 0.038-0.071 mg/kg). After the patients were injected intravenously with 0.04 mg/kg of midazolam, the respiratory and circulatory systems were basically stable, no serious adverse events occurred, and the forgetting rate was 88.5%. ET50 (the time for half of the subjects in a state of forgetfulness) was 23.77 minutes (95% CI: 20.18-27.07 min), and the corresponding BIS was 83.22; ET05 (the time for 5% of the subjects in a state of forgetfulness) was 53.90 minutes (95% CI: 48.54-61.47 min) and the corresponding BIS was 91.38. The amnesia-inducing effect of midazolam was correlated to sedation grade, BIS and age, and was not correlated to visual memory or auditory memory. In this study, the ED50 , ED95 and maintenance time of the forgetting effect of intravenous midazolam were preliminarily determined. Amnesia, Duration of amnesia, ED50, Midazolam.